Application of Multi-Scaling Complexity Indices of Heart Rate Variability in Sex Discrimination of Healthy Subjects - Matic, Zoran; Kalauzi, Aleksandar; Suljovrujic, Edin; Bojic, Tijana (2024 13th Conference of the European Study Group on Cardiovascular Oscillations (ESGCO), 2024)
Background. Nonlinear indices of heart rate variability (HRV) like detrended fluctuation analysis (DFA) and multiscaling entropy (MSE) proved to be very sensitive and suitable for data discrimination. In this research, we decided to test these indices in the statistical differentiation of the RRI intervals of Hypol database subjects by sex. Method. The indices of DFA α_{1}, α_{2} and α_{1} / α_{2} and MSE 1-4 and MSE _{5-10} were obtained using the Matlab algorithms; inter-fractal angle (θ) was obtained by the graphical-analytical method. Results. α_{1}, α_{1} / α_{2} and the θ had a higher value in male compared to female subjects. The θ angle had a significantly lower p value (when comparing sex using the Mann Whitney test) in respect to α 1 and α 2, and slightly higher in respect to α_{1} / α_{2}. MSE indices showed no sex differences. Conclusion. DFA fractal scaling indices possess sufficient sensitivity to discriminate data by sex.